UJI KONSENTRASI EKSTRAK DAUN BINTARO (Cerbera Manghas) TERHADAP HAMA KUTU PUTIH (Paracoccus Marginatus) PADA PEMBIBITAN EKALIPTUS (Eucalyptus Pellita) PT. ARARA ABADI DISTRIK SOREK - Agnes Rahmadani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Alternative use of insecticides from natural ingredients that are safe, relatively inexpensive and easily obtained, as the leaves Cerbera manghas. This study was conducted to determine the effect of leaf extract Cerbera manghas as botanical insecticides against the pest control Paracoccus marginatus on nursery Eucalyptuspellita, and get the concentration of the best of the level of mortality of pest Paracoccus marginatus on nursery Eucalyptuspellita. This research method using a completely Randomized Design consisting of four treatments and four replicates so that there are 16 units of the experiment. The treatment in this study include the concentration of the leaf extract Cerbera manghas 30 g/l of water, the concentration of 40 g/l of water, the concentration of 50 g/l of water and control. Parameters measured in this study is the starting time of the death of the insect test, the lethal time (LT50), the mortality daily, total mortality as well as temperature and humidity. Data analysis was performed using analysis of variance for a completely randomized design one of the factors using SPSS 20.0. Furthermore, if the treatment gave a real effect on the productivity of pine resin, then test the map in the form of Test Duncan's New Multiple Range Test (DNMRT) at the level of 5%. The concentration of leaf extract Cerbera manghas 50 g/l of water is the concentration of the best in controlling Paracoccus marginatus with the results of the preliminary time of death of the insect test the fastest way is 9.25 hours, the best time lethal to 50% (LT50) Paracoccus marginatus is 29,50 hours and total mortality amounted to 100.00%. Keywords: Cerbera manghas, Paracoccus marginatus, Eucalyptus pellita, Leaf Extract.